Shelleyan writing materials in the Bodleian Library: a catalogue of formats, papers, and watermarks - Barker-Benfield, B (Routledge, 2002)
Papers used in the autograph notebooks, home-made booklets, loose sheets and letters of Percy Bysshe Shelley, Harriet Shelley, Mary Wollstonecraft Shelley (to Dec. 1823), and Claire Clairmont (to Sept. 1822), held at the Bodleian Library in its own collections and in the Abinger deposit, with indexes of watermarks and of other features When the project to publish facsimiles of the Bodleian Shelley manuscripts was proposed in the early 1980s, it was soon agreed that the series should be organized by form rather than by content. The manuscript, not the text, would be the organizing principle: instead of bring ing together selected images of the drafts and fair copies of a given work, the series would reproduce each Shelleyan notebook entire and in order, together with systematic coverage of the residues of loose papers. This decision was already almost dictated by the Shelleys' working methods and by the jumbled contents of their notebooks, and has justified itself in many ways as the series has progressed. Even the best-known poems and prose works have gained from being reproduced in context, whilst the more obscure jottings and drawings have not been left aside; the writers' choices of format, whether in note book, home-made booklet or loose sheets, have helped to throw light on the level of intention, from first draft to printer's copy; and the subtle interplay between format and content can begin to be observed.